URGENSI PEMBELAJARAN SEJARAH KEBUDAYAAN ISLAM DALAM PENGEMBANGAN KARAKTER SISWA - Miftahur Rohman (Hikmah: Journal of Islamic Studies, 2022)
AbstractThe purpose of this study is to describe the urgency of learning Islamic Cultural History as a way to instill or improve student character. This research is qualitative research with a library research approach, with data sources coming from books, scientific articles published in journals, and so on. In Article 3 of Law Number 20 of 2003 concerning the National Education System, it is stipulated that national education is the development of competencies related to the formation of people's lives and the formation of a dignified national disposition and civilization. National education develops the potential of students to have faith and piety in God Almighty, have a noble character, become healthy, knowledgeable, capable, creative, independent, democratic, and responsible citizens. That is, it can be said that the purpose of education is not only to improve the cognitive abilities of students, but also to shape the character of students. This becomes important given the large number of juvenile delinquency phenomena or even criminal acts involving children. The results of this study show that the subject of Islamic Cultural History plays a vital role in the process of internalizing character education or instilling moral values to students. This is because even in the material provided, the value of this value can be learned from the Prophet Muhammad SAW, Khulafaurrasyidin, and other major Islamic figures.AbstrakTujuan dari penelitian ini adalah untuk mendeskripsikan urgensi pembelajaran Sejarah Kebudayaan Islam sebagai salah satu cara untuk menanamkan ataupun meningkatkan karakter siswa. Penelitian ini adalah penelitian kualitatif dengan pendekatan kepustakaan atau library research, dengan sumber datanya berasal dari buku, artikel ilmiah yang diterbitkan dalam jurnal, dan sebagainya. Dalam Pasal 3 Undang-Undang Nomor 20 Tahun 2003 tentang Sistem Pendidikan Nasional ditetapkan bahwa pendidikan nasional adalah pengembangan kompetensi yang berkaitan.  dengan pembentukan kehidupan masyarakat dan pembentukan watak serta peradaban bangsa yang bermartabat. Pendidikan nasional mengembangkan potensi peserta didik agar beriman dan bertakwa kepada Tuhan Yang Maha Esa, berakhlak mulia, menjadi warga negara yang sehat, berilmu, cakap, kreatif, mandiri, demokratis, dan bertanggung jawab. Artinya, dapat dikatakan bahwa tujuan pendidikan tidak hanya untuk meningkatkan kemampuan kognitif siswa, namun juga membentuk karakter siswa. Ini menjadi penting mengingat banyaknya fenomena kenakalan remaja atau bahkan tindak kriminal yang melibatkan anak-anak. Hasil dari penelitian ini menunjukkan bahwa mata pelajaran Sejarah Kebudayaan Islam memegang peranan yang vital dalam proses internalisasi pendidikan karakter atau penanaman nilai nilai moral kepada siswa. Hal ini karena di materi yang diberikan pun, nilai nilai tersebut dapat dipelajari dari Nabi Muhammad SAW, Khulafaurrasyidin, maupun tokoh-tokoh besar Islam lainnya.